Composite phase change materials improve the photo-thermal effects of cotton fabrics. Issue 11 (June 2021) - Zhang, Wei; Hao, Shang; Weng, Jiali; Zhang, Yibo; Yao, Jiming; Wei, Sainan
We report on the impregnation-based preparation of composite phase change materials (CPCMs) with thermal storage properties, using paraffin wax and multi-walled carbon nanotubes (MWCNTs). We coated the CPCMs on the fabric by scraper coating, then evaluated their shape stability, latent heat, thermal conductivity, thermal storage stability and photo-thermal effects. Results show that CPCMs with 10% acid-oxidized MWCNTs introduce only a small phase leakage when heated at 50℃ for 900 s; their latent heat energy reduces by 16.5%, while their thermal conductivity increases by 131.9% compared to pure paraffin. When exposed to sunlight at an ambient temperature of 12.5℃, the cotton fabrics coated with CPCMs record a 12.8℃ higher surface temperature than the pristine fabric, while their heat dissipation is delayed by 120–180 s. The fabric surface temperature increases to twice the ambient temperature during daytime. Overall, these findings indicate that the coated fabric has excellent thermal stability, affirming its potential as photo-thermal functional material.